Disbalance between mortality and non-fatal vascular events in the CHAMPION-PHOENIX trial: The cangrelor efficacy challenge - Serebruany, Victor L.; Pokov, Alex N.; Fortmann, Seth D.; DiNicolantonio, James J. (Thrombosis and Haemostasis, 2014)
The recently published, largest trial with cangrelor, the Cangrelor versus Standard Therapy to Achieve Optimal Management of Platelet Inhibition (CHAMPION)-PHOENIX, suggested that the experimental agent significantly reduced the rate of stent thrombosis (ST) and myocardial infarction (MI) during PCI at 48 hours (h) and 30 days. However, the declared impressive cangrelor vascular non-fatal benefit was contradicted by identical deaths at 48 h, and a trend toward excess mortality at 30 days. We analysed the mismatch between outcomes in the CHAMPION-PHOENIX trial. The trial reported identical mortality (18 death in each arm; odds ratio [OR] 1.00 (0.52–1.92); p>0.999) at 48 h, but more deaths, 60 vs 55, after cangrelor at 30 days. There was a significant reduction of ST from 0.8% (n=46) of the patients in the cangrelor group versus 1.4% (n=74) in the clopidogrel group (odds ratio, 0.62; 95% CI, 0.43 to 0.90; p= 0.01) at 48 h, and a persistent but less impressive ST prevention benefit OR of 0.68 (0.50=0.92, p = 0.01) at 30 days. There were also 48 less MI’s following cangrelor usage enforced by a significant difference (odds ratio 0.80 (0.67–0.97) p = 0.02), which was also less prevalent at 30 days (OR 0.82 (0.68–0.98), p = 0.03). The reported ST/MI advantage should result in at least a trend towards numerically less deaths after cangrelor at 30 days follow-up, which was opposite of the results reported in CHAMPION- PHOENIX trial. Efficacy of cangrelor is challenged by the disproportional “reduction” of ST and MI conflicting with identical mortality at 48 h and worsened at day 30 fatalities. The dissociation between vascular mortality and non-fatal vascular ischaemic occlusions, unless compensated by some other unreported cause(s) of death, should be explored and explained. Unadjudicated 30-day outcomes, and all ST types should be fully disclosed. The ongoing FDA cangrelor review should focus on appropriate event count and/or possible mismatch between site-reported and extra adjudicated events in the CHAMPION-PHOENIX trial.
Keywords: Cangrelor; stent thrombosis; myocardial infarction; efficacy; mortality; clinical trials